1964
DOI: 10.1115/1.3677584
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Reynolds Number Effects in Turbomachines

Abstract: Typical space power units have a tendency to encounter low Reynolds numbers in the last turbine stages. Comprehensive test data on the effect of low Reynolds numbers on the efficiency of turbomachines are lacking. An attempt is made to assess this influence, using conventional aerodynamic arguments. By distinguishing between viscous and nonviscous losses some tentative values have been calculated which are in fair agreement with the few available test data. These considerations indicate that the stage pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1965
1965
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…This information is obtained by interpolating the corresponding n s vs. d s chart for maximum compressor efficiency (also Cordier line, sohwn dashed red in Fig. 4) in the range of application of radial turbomachinery (50<n s,c <100) [54]. The specific diameter (d s,c ) so obtained is used to calculate the tip diameter of the compressor impeller (d tip,c ).…”
Section: Turbomachinerymentioning
confidence: 99%
See 1 more Smart Citation
“…This information is obtained by interpolating the corresponding n s vs. d s chart for maximum compressor efficiency (also Cordier line, sohwn dashed red in Fig. 4) in the range of application of radial turbomachinery (50<n s,c <100) [54]. The specific diameter (d s,c ) so obtained is used to calculate the tip diameter of the compressor impeller (d tip,c ).…”
Section: Turbomachinerymentioning
confidence: 99%
“…Specific speed vs. specific diameter compressor showing the Cordier line for radial stages in dashed red. Adapted from[54] …”
mentioning
confidence: 99%
“…The other one of performance prediction is as follows: First, each loss generated within the compressor stage is estimated by recognizing the individual relationship between it and the velocity distribution, the Reynolds number as well as Mach number. Afterwards, the final result can be estimated by superimposing them [7][8][9][10][11]. Though the latter method has a troublesome defect that eacit loss has to be calculated one by one, it has also remarkable advantages in that the latter method can be used to predict the performance levels over the part load operating conditions of the compressor, and the latter method enable application for performance prediction of new type compressor ( that is, nref in eqation (1) is not yet known ), while nref has to be known in case of the former.…”
Section: _nmentioning
confidence: 99%
“…This value seems to have been established as the lower limit of this parameter for operation without reduction in efficiency due to Reynolds-number influence. In Fig.l, which is reproduced from a recent paper by Balje (1) it is shown that the choice of working fluid has a strong influence on the Reynolds number encountered in turbomachinery, with hydrogen and helium producing the lowest values of the ratio Re D /H p for turbine:; operating with an inlet temperature of 1500 F at a speed of 20,000 rpm. In the case of multistage reentry turbines operating on hydrogen with a typical specific speed of around 10 to 15 and a power output per stage of around 10 hp, it will be seen that Fig•1 predicts a tip speed Reynolds number of around 10,000 which corresponds to a blade chord Reynolds number in the range 800 to 1600.…”
mentioning
confidence: 90%